On the application of storage coefficient determination by quasi-steady-state flow - Birpinar, ME; Gazioglu, A (I W A PUBLISHING, 2005)
A simple analytical method has been used for estimating the storage coefficient provided that transmissivity of the aquifer is known at the quasi-steady-state condition in confined or unconfined aquifers. The application of the method has been performed for unconfined and confined aquifer test data in Chaj Doab, Pakistan with observation wells and compared with conventional methods in the groundwater flow literature dealing with pumping tests. The results from the methodology presented in this paper conform well in practice with the results obtained from the traditional methods on the basis of order of magnitude.
Keywords: aquifers; groundwater; quasi-steady state; storativity; well; LARGE-DIAMETER; Water Resources